Effectiveness of iodine for continuous decontamination of dental unit waterline - Chatchaya Petchphayaprai; Chutimon Chotipan; Pitchayapa Sa-ngiampak; Kittisak Thotsaporn; Ruchanee Salingcarnboriboon Ampornaramveth (Nature Publishing Group, 2023)
Abstract Objective Dental Unit Waterlines (DUWLs) are contaminated by various species of microorganisms. DUWLs should be disinfected appropriately to control microbial contamination. This study investigated the effectiveness of devices continuously releasing iodine to control microbial contamination in DUWLs. Materials and methods Ten dental chair units (DCU) at Chulalongkorn University were randomized into the iodine and control groups. After setting iodine treatment devices, the DCU was allowed to operate normally. 25 ml of water from airotors lines were collected weekly for enumerating bacteria. The viability of biofilms in DUWLs was quantified by ATP testing kit. The amount of iodine released into the procedural water was also quantified. Results The continuous presence of iodine could significantly control bacterial contamination in the DUWL to be less than 500 CFU/mL, the standard level recommended by the Centre for Disease Control and Prevention (CDC). Iodine treatment can reduce bacterial CFU up to 98-100%. Biofilm viability in the iodine group was slightly lower than that of the control group though not statistically significant. After eleven months, the average iodine release was measured to be 3.6 ppm which is still effective in controlling bacterial contamination. Conclusion Continuously supplying iodine in DUWLs effectively controls microbial contamination.